Like putting out fires: Saving a secretive endangered snake from extinction - Salo Pälvi (European Snake Society, 2022)
The narrow-headed gartersnake (Thamnophis rufipunctatus) is a non-venomous, highly aquatic snake species that feeds exclusively on fish. Its distribution is limited to two primary watersheds in the states of Arizona and New Mexico in the USA, where the species is federally listed as ‘threatened’. The population has declined due to a multitude of factors, including killing by humans, habitat degradation and destruction, competition with and predation by nonnative species, changes in aquatic habitat after forest fires, and inbreeding due to increasing
isolation. However, recent successes in captive breeding as well as translocation and release of captive-born individuals give hope for the species’ survival.